The Centers of the Universal Enveloping Algebras for Contracted Lie Groups. - Wolak, Mathew. (2017)
Abstract: Lie group contraction is a process by which Lie groups are ''flattened out''. This thesis finds the algebra of bi-invariant differential operators (identified with the center of the universal enveloping algebra) for the Galilean group (which is a contraction of the Poincare group).; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Mathematics.; Advisor: Fulton Gonzalez.; Committee: Fulton Gonzalez, George McNinch, and Tomoyuki Kakehi.; Keyword: Mathematics.